Views on Sex and Sex Education Among Gang-Involved Latino Youth in the United States. (May 2014) - Kassab, Veronica A.; Acevedo-Polakovich, Ignacio D.; Grzybowski, Megan M.; Stout, Stacy; Richards, Allyn E.; Barnett, Miya L.; Guerra-Morales, Aileen; Bell, Katrina M.; Crider, Elizabeth A.; Beck, Kara L.; Brookins-Fisher, Jodi; Alfaro, Mario; et al.
Although gang-involved Latino youth in the United States are uniquely at risk of adverse consequences from sexual behavior, little research is available that can guide those who wish to develop interventions to reduce sexual risk among these youth. To facilitate the development of effective interventions, we identified cultural and contextual factors that influence sexual behavior and sex education among gang-involved Latino youth in one U.S. community. By analyzing transcripts from interviews and focus groups with three different groups of key stakeholders—gang-experienced Latino youth, the parents of gang-experienced Latino youth, and the personnel of a program providing comprehensive human services for gang-involved Latino youth—we identified three domains to be considered in developing sexual risk-reduction interventions for gang-involved U.S. Latino youth. The focus of our discussion is on the implications of these findings for future development or adaptation of interventions.